PERSEPSI PUBLIK TENTANG OLAHRAGA ANGKAT BEBAN DI TIKTOK FIT AND FLEX GYM - Bezaleel Syafa Chrisandy; Mareta Puri Rahastine (PT. Hasba Edukasi Mandiri, 2025)
In 2016, more than 1.9 billion people worldwide aged 18 and older had obesity problems, with 39% of them being men and 40% being women who were overweight, according to data from the World Health Organization (WHO). Of this total, 11% of men and 15% of women were identified as obese, meaning that approximately 650 million people suffer from severe obesity. Social media platforms serve as communication tools with a wide reach and significant influence on individual thought patterns and actions. Therefore, it is crucial to study the role of social media in conveying messages related to sports and health to the public. This study was conducted at Fit And Flex Gym in Bekasi to Understanding how members perceive content related to weightlifting and weight loss. Using the Social Construction of Reality Theory, it is explained that perception is shaped through social processes involving interaction and public communication, which include elements of externalization, objectification, and internalization. Using qualitative descriptive research methods, including in-depth interviews, documentation, and direct observation of four informants with diverse backgrounds, the results of this study confirm that the role of social media, particularly TikTok, in relation to weightlifting has shaped positive perceptions toward social media content about weightlifting and weight loss.